2D Animation on Being New Parent - Pratama, Jimmy; Kelvin, Kelvin (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2025)
The transition to parenthood is a multidimensional challenge that often causes emotional and practical stress for new parents, particularly in understanding proper infant care. This study aims to address these issues by developing a 2D animated educational video titled "Being a New Parent". The video serves as an engaging visual medium to educate young couples about essential baby care practices, including hygiene, feeding, diaper changing, bonding, and sleep management. The animation was developed using the Multimedia Development Life Cycle (MDLC) method, consisting of six stages: concept, design, material collection, assembly, testing, and distribution. Production involved professional software including Adobe Illustrator for asset design, Adobe After Effects for animation, and Adobe Premiere Pro for final editing and audio integration. The final product is a 2-minute and 8-second video distributed via YouTube. Evaluation through interviews with new parents revealed that the animation effectively increased understanding of parenting basics, though suggestions for more detailed and context-sensitive content were noted. The results demonstrate that 2D animation is a powerful tool for digital parenting education, capable of simplifying complex information into a relatable and accessible format for the millennial generation.